Analysis of Mathematic Creative Thinking Ability and Metacognition of Student on Probing Prompting Learning Models with Scaffolding Strategy - Sulistyawati, Anita; Dwijanto, Dwijanto; Walid, Walid (Universitas Negeri Semarang, 2018)
This study aimed to: (1) examine the effectiveness of the learning probing prompting model with scaffolding strategy on mathematical creative and metacognitive thinking skills, (2) examine the effect of metacognition on mathematical creative thinking skills with probing prompting model learning with scaffolding strategy, (3) describing ability on mathematical creative thinking in terms of students' metacognition with probing prompting model learning with scaffolding strategy. This research was a mixed method type with concurrent embedded design. Population in this study were students of class VII SMP Negeri 7 Semarang in the academic year of 2017/2018. The results showed that probing prompting model learning with scaffolding strategies was effective for mathematical creative and metacognitive thinking skills. Metacognition had a positive effect on mathematical creative thinking ability by probing prompting models learning with scaffolding strategies. A student with high metacognition was able to meet four indicators maximally and perfectly, while another one met one indicator well, but for the other three indicators he is able to master well, there were only a few errors. Students with middle-metacognition ability were able to meet two indicators maximally, but cannot fulfill the other two indicators. Students with low metacognition were able to fulfill one indicator maximally and could not fulfill the other three indicators.